2002
DOI: 10.1152/ajpheart.01109.2001
|View full text |Cite
|
Sign up to set email alerts
|

Nonreentrant focal activations in pulmonary veins in canine model of sustained atrial fibrillation

Abstract: The mechanisms are unclear. We induced sustained (Ͼ48 h) AF by rapidly pacing the left atrium (LA) in six dogs. Highdensity computerized mapping was done in the PVs and atria. Results show repetitive focal activations in all dogs and in 12 of 18 mapped PVs. Activation originated from the middle of the PV and then propagated to the LA and distal PV with conduction blocks. The right atrium (RA) was usually activated by a single large wavefront. Mean AF cycle length in the PVs (left superior, 82 Ϯ 6 ms; left infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
1
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 37 publications
(38 reference statements)
6
90
1
3
Order By: Relevance
“…14 We simultaneously mapped the LA free wall at the junction of the left superior pulmonary vein (LSPV), the Bachmann's bundle (BB), and the lateral RA free wall ( Figure 1A). …”
Section: High-density Computerized Mapping Of Afmentioning
confidence: 99%
“…14 We simultaneously mapped the LA free wall at the junction of the left superior pulmonary vein (LSPV), the Bachmann's bundle (BB), and the lateral RA free wall ( Figure 1A). …”
Section: High-density Computerized Mapping Of Afmentioning
confidence: 99%
“…21) Non-reentrant focal activations have also been reported in the PVs of a canine model of pacing-induced sustained AF. 22) These observations might partially explain the lower initial success rate of AF termination in the present study. However, our study showed a high rate of late AF termination in the chronic phase despite the failure to acutely terminate AF by RA linear ablations (Table I).…”
Section: )mentioning
confidence: 66%
“…16 The mechanisms responsible for the abnormal impulse activity have been the source of several investigations. [17][18][19][20][21][22][23] Triggered activity may be particularly important. [19][20][21][22][23] Ranolazine is an anti-anginal agent, which inhibits the normal and abnormal late Na+ channel current in the ventricle and the peak Na+ channel current in the atrium.…”
Section: 2mentioning
confidence: 99%
“…[17][18][19][20][21][22][23] Triggered activity may be particularly important. [19][20][21][22][23] Ranolazine is an anti-anginal agent, which inhibits the normal and abnormal late Na+ channel current in the ventricle and the peak Na+ channel current in the atrium. [24][25][26] By this inhibition, it affects intracellular calcium handling, producing an energy sparing effect.…”
Section: 2mentioning
confidence: 99%